2018
DOI: 10.1162/tacl_a_00028
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Evolution of a Scientific Field through Citation Frames

Abstract: Citations have long been used to characterize the state of a scientific field and to identify influential works. However, writers use citations for different purposes, and this varied purpose influences uptake by future scholars. Unfortunately, our understanding of how scholars use and frame citations has been limited to small-scale manual citation analysis of individual papers. We perform the largest behavioral study of citations to date, analyzing how scientific works frame their contributions through differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
194
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 169 publications
(199 citation statements)
references
References 51 publications
5
194
0
Order By: Relevance
“…We note that these results were obtained without using hand-curated features or additional linguistic resources as used in Jurgens et al (2018). We also experimented with adding features used in Jurgens et al (2018) to our best model and not only we did not see any improvements, but we observed Table 4 shows the main results on SciCite dataset, where we see similar patterns. Each scaffold task improves model performance.…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…We note that these results were obtained without using hand-curated features or additional linguistic resources as used in Jurgens et al (2018). We also experimented with adding features used in Jurgens et al (2018) to our best model and not only we did not see any improvements, but we observed Table 4 shows the main results on SciCite dataset, where we see similar patterns. Each scaffold task improves model performance.…”
Section: Resultsmentioning
confidence: 53%
“…To address these problems and to unify previous efforts, in a recent work, Jurgens et al (2018) proposed a six category system for citation intents. In this work, we focus on two schemes: (1) the scheme proposed by Jurgens et al (2018) and (2) an additional, more coarse-grained generalpurpose category system that we propose (details in §3). Unlike other schemes that are domainspecific, our scheme is general and naturally fits in scientific discourse in multiple domains.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…More recent corpora have been annotated at phrasal level. SciCite [9] and ACL ARC [21] are datasets for citation intent classification from Computer Science, Medicine, and Computational Linguistics. ACL RD-TEC [18] from Computational Linguistics aims at extracting scientific technology and non-technology terms.…”
Section: Scientific Corporamentioning
confidence: 99%